Effect of local extension sites on survival in locally advanced maxillary sinus cancer. Issue 11 (18th December 2013) - Kano, Satoshi; Hayashi, Ryuichi; Homma, Akihiro; Matsuura, Kazuto; Kato, Kengo; Kawabata, Kazuyoshi; Monden, Nobuya; Hasegawa, Yasuhisa; Onitsuka, Tetsuro; Fujimoto, Yasushi; Iwae, Shigemichi; Okami, Kenji; et al.
Abstract Background We analyzed the effects of local extension sites on survival in patients with locally advanced maxillary sinus cancer. Methods The criteria for inclusion in this study were as follows: (1) previously untreated maxillary sinus cancer; (2) squamous cell carcinoma; (3) T4 disease; and (4) curative‐intent treatment. The data for 118 patients were obtained from 28 institutions across Japan and analyzed for overall survival and local control rates by local extension site. Results Sites with a poor prognosis included the cribriform plate, dura, nasopharynx, middle cranial fossa, and cranial nerves other than V2. There was a significant correlation among these sites, except for the cranial nerves. Additionally, the hard palate was the only site that correlated with nodal involvement and showed a poor treatment outcome. Conclusion Even in cases presenting with similar T4 maxillary sinus cancer, treatment should be performed in consideration of the local extension site. © 2013 Wiley Periodicals, Inc. Head Neck 36: 1567–1572, 2014